Cybertherapy : internet and virtual reality as assessment and rehabilitation tools for clinical psychology and neuroscience - Riva, G. (Amsterdam ; Washington, D.C. : IOS Press, 2004)
Cybertherapy, the integration of telehealth technologies with the Internet and shared virtual reality, is used for two reasons: either because there is no alternative, or because it is in some sense better than traditional medicine.
Preface / A. Barak -- Introduction / G. Riva, C. Botella, P. Legeron and G. Optale -- Cybertherapy Rationale: Advantages of New Technologies for Clinical Psychology -- Cybertherapy in Practice: The VEPSY Updated Project / G. Riva, C. Botella, G. Castelnuovo, A. Gaggioli, F. Mantovani and E. Molinari -- New Tools in Cybertherapy: the VEPSY Website / G. Castelnuovo, C. Buselli, R. De Ferrari, A. Gaggioli, F. Mantovani, E. Molinari, M. Villamira and G. Riva -- Virtual Reality and Psychotherapy / C. Botell, S. Quero, R.M. Banos, C. Perpina, A. Garcia Palacios and G. Riva -- Virtual Interaction in Cognitive Neuropsychology / F. Morganti -- Cybertherapy Experiences: Clinical Trials in the Treatment of Mental Disorders -- The Use of VR in the Treatment of Panic Disorders and Agoraphobia / C. Botella, H. Villa, A. Garcia-Palacios, S. Quero, R.M. Banos and M. Alcaniz -- Virtual Reality Exposure in the Treatment of Social Phobia / E. Klinger, P. Legeron, S. Roy, I. Chemin, F. Lauer and P. Nugues -- The Use of VR in the Treatment of Eating Disorders / G. Riva, M. Bacchetta, G. Cesa, S. Conti and E. Molinari -- Male Sexual Dysfunctions: Immersive Virtual Reality and Multimedia Therapy / G. Optale, M. Pastore, S. Marin, D. Bordin, A. Nasta and C. Pianon -- Cybertherapy Technology: Advanced Tools for Clinical Psychology -- New Technologies for Providing Remote Psychological Treatments / B. Rey, M. Alcaniz and J.A. Lozano -- Technological Background of VR / M. Alcaniz, J.A. Lozano and B. Rey -- Cybertherapy Ergonomics: How to Design Effective Cybertherapy Tools -- Ergonomics of Virtual Environments for Clinical Use / A. Spagnolli, L. Gamberini, P. Cottone and G. Mantovani -- An Integrated Approach to the Ergonomic Analysis of VR in Psychotherapy: Panic Disorders, Agoraphobia and Eating Disorders / C. Galimberti, G. Belloni, A. Cattaneo, M. Grassi, V. Manias and L. Menti -- The Future of Cybertherapy: New Scenarios and Applications -- Immersive Virtual Telepresence: Virtual Reality Meets eHealth / G. Riva, F. Morganti and M. Villamira -- The Future of Cybertherapy: Improved Options with Advanced Technologies / B.K. Wiederhold and M.D. Wiederhold.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Clinical psychology -- Data processing; Internet; Virtual reality; Mental illness -- Treatment; Psychotherapy -- methods; Internet; Mental Disorders -- therapy; Virtual Reality; Psychologie clinique -- Informatique; Internet; Réalité virtuelle; Maladies mentales -- Traitement; Internet; virtual reality; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Psychopathology -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; Mental illness -- Treatment; Clinical psychology -- Data processing; Internet; Virtual reality; Informatique médicale.; Klinische Psychologie; Medizin; Virtuelle Realität; Therapieën.; Internet; Klinische psychologie; Neurologie; Médecine -- Informatique; Neurosciences -- Informatique; Psychologie clinique -- Informatique; Andre fag (naturvidenskab og teknik) -- Andre fag; Aufsatzsammlung